2018
DOI: 10.1089/fpd.2017.2356
|View full text |Cite
|
Sign up to set email alerts
|

Propidium Monoazide Quantitative Real-Time Polymerase Chain Reaction for Enumeration of Some Viable but Nonculturable Foodborne Bacteria in Meat and Meat Products

Abstract: Foodborne infections due to bacterial pathogens are increasing worldwide. Given the surreptitious nature of viable but nonculturable (VBNC) bacteria, they largely remain a threat to public health and food safety due to their non-detectability through conventional plate count techniques. Hence, species-specific quantitative real-time polymerase chain reaction (PCR) (qPCR) alone and combined with the use of propidium monoazide (PMA) was used along with the plate count method to quantify VBNC Staphylococcus aureu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
6
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 30 publications
2
6
0
1
Order By: Relevance
“…No significant difference was observed in VBNC detection for all three spiked samples, supporting the real-time application of the proposed assay for multiple matrices with reliable reproducibility. Our results support and extend the results from previous studies in determining dead/live or VBNC E. coli O157:H7 in various complex matrices combining PMA dye with LAMP, qPCR, and PCR [ 1 , 4 , 10 , 14 , 46 , 54 ]. Some reports suggest that VBNC cells can reacquire their active state and become viable in the presence of nutrients and favourable conditions, However, no resuscitation of E. coli O157:H7 cells was observed in the presented study when VBNC cells were transferred to water, apple juice, and milk [ 11 , 15 , 46 ].…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…No significant difference was observed in VBNC detection for all three spiked samples, supporting the real-time application of the proposed assay for multiple matrices with reliable reproducibility. Our results support and extend the results from previous studies in determining dead/live or VBNC E. coli O157:H7 in various complex matrices combining PMA dye with LAMP, qPCR, and PCR [ 1 , 4 , 10 , 14 , 46 , 54 ]. Some reports suggest that VBNC cells can reacquire their active state and become viable in the presence of nutrients and favourable conditions, However, no resuscitation of E. coli O157:H7 cells was observed in the presented study when VBNC cells were transferred to water, apple juice, and milk [ 11 , 15 , 46 ].…”
Section: Discussionsupporting
confidence: 90%
“…Our results support and extend the results from previous studies in determining dead/live or VBNC E. coli O157:H7 in various complex matrices combining PMA dye with LAMP, qPCR, and PCR [ 1 , 4 , 10 , 14 , 46 , 54 ]. Some reports suggest that VBNC cells can reacquire their active state and become viable in the presence of nutrients and favourable conditions, However, no resuscitation of E. coli O157:H7 cells was observed in the presented study when VBNC cells were transferred to water, apple juice, and milk [ 11 , 15 , 46 ]. The revival capacity of different cells may vary with different food matrices or environmental conditions.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…This aligns with previous research ( Enayat et al, 2012 ; Elhawary et al, 2016 ) in which Enterobacterales isolates were detected in meat samples with percentages of 67 and 54%, respectively. However, Abd El-Aziz et al (2018) reported Enterobacterales in 80.33% of examined meat samples. The variations in the results obtained by different investigators may be due to differences in handling, manufacturing practices, and the time of exposure.…”
Section: Discussionmentioning
confidence: 93%
“…When milk samples were inoculated with 3 × 10 4 cfu/ml of viable S. agalactiae cells and 3 × 10 3 cfu/ml of dead cells or 3 × 10 3 cfu/ml of viable cells and 3 × 10 4 cfu/ml of dead cells, the difference in results for PMA–qPCR compared with SDS–PMA–qPCR indicated that the presence of dead cell debris with an intact outer membrane was more efficiently affected by the SDS–PMA combination than by PMA alone. Previous studies showed that DNA of dead cells of various pathogens in milk, meat homogenates or water samples can be inactivated for PCR by treatment with PMA or SDS–PMA (Tomás et al, 2009; Gensberger et al, 2014; El-Aziz et al, 2018). Compared with these reports, the PMA–qPCR assay with SDS developed in the present study was faster and had higher sensitivity than previously reported methods.…”
Section: Discussionmentioning
confidence: 99%